Calcium score in COVID-19 patients: A risk predictor for severity of lung involvement? (Annals of Medical Research, 2022)
Aim: The aim of the study is to evaluate the relationship between the severity of lung involvement and the Agatston score calculated using the chest computed tomography (CT) images of patients diagnosed with COVID-19 pneumonia.Materials and Methods: One hundred thirty-six patients (71 male, 65 female; mean age: 51,45 years ± 16,06) presented to our hospital between March 17, 2020, and April 14, 2020, and got the diagnosis of COVID-19 pneumonia, were included in the study. The patients were stratified into two disease severity groups, namely mild disease (n=118) and severe disease (n=18), based on their ICU needs. Agatston score and visual CT score, which were calculated using the CT images obtained at admission, were assessed.Results: Calcified coronary plaques were observed in 47 patients (34.6%). Agatston score ranged from 0.8 to 5179 in these patients (n=47, median: 125.8). Overall, there was a significant, moderately positive correlation between Agatston score and visual CT score (n=136, p < 0.001). Visual CT score was significantly higher in patients with calcified plaques (n=47, p < 0.001). Among the patients with calcified plaques, the Agatston and visual CT scores were significantly higher in the severe disease group (n=9) than the mild disease group (n=38) (p=0.015 and p=0.023, respectively).Conclusion: Agatston score calculated from CT images can be used as a risk indicator in predicting the severity of COVID-19 pneumonia.
Keywords: COVID-19; coronary artery; computed tomography